The Influence of Company Size, Company Growth, Price to Book Value, Investment Opportunity Set, and Operating Cash Flow Againts Price Earnings Ratio in Food and Beverage Sub Sector Manufacturing Companies Listed In BEI from 2015 To 2017 - Andini Nurwulandari (Budapest International Research and Critics University, 2021)
This study aims to see how the Price Earning Ratio is affected by company size, growth, price to book value, investment opportunity set, and operating cash flow. The authors used panel data regression to analyze data from 2015 to 2017, 13 food and beverage firms were listed on the Indonesia Stock Exchange. According to the data that have been collected, company size, company growth, and price to book value all have a positive and significant effect on the Price Earning Ratio. Meanwhile, the Investment Opportunity Set and Operating Cash Flow have no impact on the Price Earning Ratio.